The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1364/ao.53.004413
|View full text |Cite
|
Sign up to set email alerts
|

1  kW peak power, 110  ns single-frequency thulium doped fiber amplifier at 2050  nm

Abstract: We report a high power, single frequency, linearly polarized master oscillator power amplifier emitting 110 ns, 1 kW peak power pulses at 2050 nm. A 20% slope efficiency and a beam quality of M2=1.21 are achieved with three-stage double-clad Tm(3+)-doped fiber architecture. Various pump schemes are compared leading to the conclusion that 793 nm pump wavelength is the most efficient for amplification at 2050 nm. Based on numerical simulations, the Brillouin gain coefficient around 2 μm in Tm(3+) highly doped si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It is known that the central frequency of the lorentzian Brillouin gain curve can be shifted by applying strain to the fiber. Applying an optimal strain distribution for a given signal distribution in the fiber will result in a flat Brillouin spectrum and a larger threshold [6]. We have shown that a triangular distribution can be used.…”
Section: Preliminary Version Of the High Power Fiber Transmittermentioning
confidence: 98%
“…It is known that the central frequency of the lorentzian Brillouin gain curve can be shifted by applying strain to the fiber. Applying an optimal strain distribution for a given signal distribution in the fiber will result in a flat Brillouin spectrum and a larger threshold [6]. We have shown that a triangular distribution can be used.…”
Section: Preliminary Version Of the High Power Fiber Transmittermentioning
confidence: 98%
“…We developed a high power single-frequency laser source at 2050 nm using strain gradient to mitigate SBS [25]. The pumping scheme selected for the amplifier is clad pumping using 793 nm laser diodes.…”
Section: High Peak Power Narrow Linewidth Mopfa Emitting At 2050 Nmmentioning
confidence: 99%
“…The value of the Brillouin gain that we have discussed so far is the Brillouin gain value obtained for a homogenous fiber length L. Among the various methods used to increase the Brillouin threshold several are based on strain [15,25] or temperature [40][41][42] change along the fiber. The principle is to shift the Brillouin gain maximum along the fiber.…”
Section: Comparison Of Brillouin Propertiesmentioning
confidence: 99%
“…A careful comparison of experiment and theory is important both for basic research and systematic engineering design of Thulium fiber amplifiers operating in the 2 µm region. Applications include LIDAR or spectroscopy, such as CO2 atmospheric absorption at 2051.4 nm 1 . Currently the state of modeling for Tm-doped fiber (TDF) amplifiers is not nearly as advanced as the state of modeling for Erbium-doped fiber amplifiers [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%